Application of Virtual Practicum Media Based on Everycircuit in Discovery Learning in Basic Electronics Course Students Physics Education Program Class of 2022 - Jusriana, Andi; Suarga, Suarga; Wahyuni, Sri; Nurnaifah, Ihfa Indira; Suarti, Suarti (Journal of Teaching and Learning Physics, 2024)
A practicum is a learning activity that involves observing an experiment or testing a concept inside or outside the laboratory. A virtual practicum is a practicum activity that is carried out virtually. The use of learning models in practicum also affects the activeness of students. One virtual practicum that can be used is Everycircuit, which uses discovery learning. The research objectives are to determine the learning outcomes of physics education study program students class of 2022 before using Everycircuit-based virtual practicum media in discovery learning in Basic Electonics courses, to determine the learning outcomes of physics education study program students class of 2022 after using Everycircuit-based virtual practicum media in discovery learning in Basic Electonics courses, and to determine the increase in learning outcomes of physics education study program students class of 2022 after using Everycircuit-based virtual practicum media in discovery learning in Basic Electonics courses. The type of research used is pre-experimental research with a one-group pretest-posttest research design. The results showed that the average value of student learning outcomes in introductory electonics courses before using Everycircuit-based virtual practicum media in discovery learning is 65.42, while the average value of student learning outcomes in introductory electonics courses after being taught using Everycircuit-based virtual practicum media in discovery learning is 90.27. The results of the N-gain test calculation obtained 0.62 with a moderate category, so it can be concluded that there is an increase in student learning outcomes in introductory electonics courses after being taught using Everycircuit-based virtual practicum media in discovery learning.